THE IDENTIFICATION OF IDIOMS IN THE NATIVE ENGLISH SPEAKERS’ ARTICLES OF THE JAKARTA POST DATED FRIDAY JUNE 19, 2015 - ., I Gede Bagus Oka Wisnaya; ., Drs. Asril Marjohan,MA; ., Nyoman Karina Wedhanti, S.Pd., M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Tujuan dari penelitian ini adalah untuk menganalisis arti dan tipe dari idiom di artikel penutur asli bahasa Inggris di The Jakarta Post tanggal Jumat, 19 Juni 2015. Langkah yang digunakan dalam mendapatkan data adalah mengidentifikasi keberadaan idiom, mengumpulkan idiom, memeriksa arti idiom melalui Cambridge Online Dictionary dan mengidentifikasi jenis-jenis idiom menggunakan teori dari Makkai. Hasil penelitian menunjukkan bahwa tidak ditemukannya Idiom of Encoding. Semua idiom yang ditemukan dari 25 artikel adalah Idiom of Decoding, 77 Lexemic Idiom, yang diantaranya 63 phrasal verb dan 14 phrasal compound dan 5 Sememic Idiom yang semuanya adalah proverb. Idiom-idiom tang ditemukan mengandung makna yang berbeda dari kata-kata yang menyusun idiom-idiom tersebutKata Kunci : idiom, artikel, The Jakarta Post The aim of this research was to identify the idiom meanings and types in the articles of the English native speakers in The Jakarta Post dated Friday June 19, 2015. The steps used to collect the data were identifying existence of idioms, collecting the idioms, checking the meanings from the Cambridge Online Dictionary and identifying the types of the idioms by using Makkai’s theory. The result showed that no Idiom of Encoding found. All of the idioms found in 25 articles were Idiom of Decoding, 77 Lexemic Idioms, in which were 63 phrasal verbs and 14 phrasal compounds and 5 Sememic Idioms which all 5 idioms were proverbs. The idioms found had different meanings from the words constructing the idiomskeyword : idioms, article, The Jakarta Post